Pengaruh Pembelajaran Aquatik dengan Metode Flipped Classroom terhadap Kepercayaan Diri Siswa SMAN 10 Bandung pada Kelas Pendidikan Jasmani - Usman Hanafi, Muhamad; Carsiwan; Rahmat, Alit (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The objective of this study is to determine the effect of the flipped classroom learning model on students’ self-confidence at SMAN 10 Bandung. The population and sample in this study consisted of 11th-grade students. The sampling technique used was cluster random sampling, which involves random sampling based on area. From the existing population, two classes were selected as samples, with each class consisting of 36 students. One class was designated as the experimental class, and the other as the control class.The method used in this study is a quasi-experimental design. Data collection was conducted using a questionnaire to assess students' self-confidence. Data were analyzed using SPSS with paired sample t-test and independent sample t-test. This research aims to find out how significant the effect of the flipped classroom learning model is on students’ self-confidence in physical education classes at SMAN 10 Bandung. The significance value obtained was 0.000 < 0.05, which indicates a significant effect of the flipped classroom learning model on students’ self-confidence in physical education classes at SMAN 10 Bandung. Before applying the flipped classroom model, the students' average self-confidence score was 57.83, which increased to 65.92 in the posttest. This increase in the average score demonstrates that the flipped classroom model has a positive effect on students' self-confidence in physical education. Conclusion, based on the results of data analysis, it can be concluded that there is a significant influence of the flipped classroom learning model on students’ self-confidence in physical education classes at SMAN 10 Bandung. Keywords: Flipped classroom model, students' self-confidence, physical education